(untitled) (Global Journal of Medical Research, 2023)
This bibliographic review evaluates Artificial Intelligence AI theory s applications in the field of Family Medicine Globally billions of people suffer from multiple health related issues throughout their lives including diseases of the heart lungs kidney diabetes and many forms of cancer Diagnosis remedy and prevention of these disorders are multifaceted and machine computer based investigative tools for doctors are immediately needed to augment their decision-making This study includes various applications of AI machine learning AI ML procedures in family medicine and its various sub-specialties AI ML-centered medicine offers better solutions over standard family medicine covering birth through end of life care These include treatments for adolescents geriatrics disorders of pain and sleep and sports injuries However several implementation hurdles for AI in clinical family medicine persist